Effect of Taichi Chuan on health-related physical fitness in adults: a systematic review with meta-analysis - Qi, Fengmeng; Kim, Geok Soh; Mohd Nasiruddin, Nasnoor Juzaily; Leong, Ong Swee; Sun, He; Liu, Huange (Elsevier, 2023)
Purpose Taichi Chuan was previously shown to benefit physical health, but the results were inconsistent. The main reason is that the mechanism is not clear and may be interpreted differently. In this systematic review, we analyzed the data obtained from various randomized controlled trials to identify the effectiveness of Taichi Chuan and the mechanism by which it improves the physical health of adults.